Nationalism, Modernization and the Polylogue of Civilizations - Kavolis, Vytautas (Sociologija. Mintis ir veiksmas, 2022)
This is a translation of the article “Nationalism, Modernization and the Polylogue of Civilizations” by Lithuanian sociologist Vytautas Kavolis. The original article was published in English in 1991 in the Comparative Civilizations Review, and the Lithuanian translation appeared in 1992 in a journal Proskyna (translated by Saulius Spurga). In this article Kavolis discusses complex relationship of nationalism and cultural configurations of modernity, postmodernity and antimodernist thinking. He considers how different forms of thinking shape the violent and humane manifestations of nationalism, and what opportunities are offered by globalization to the national identity.
Keywords: nationalism; modernization; postmodern; globalization